Toni Morrison correspondence - Morrison, Toni.
TLS (1993 March 19) from Morrison to the Library of Congress Advisory Committee on Copyright Registration and Deposit regarding her resignation from the committee.
Author. Born as Chloe Anthony Wofford in 1931.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Library of Congress. -- Advisory Committee on Copyright Registration and Deposit -- Correspondence; Authors